Estruturas de governança e inovação em sistemas agroalimentares diferenciados de carne bovina no Paraná - Guimarães, Amanda Ferreira (2017)
Considering difficulties imposed by globalization, there has emerged, as an alternative to small and medium producers, Differentiated Agri-Food Systems (DASs). These subsystems are subsystems whose organization of productive activities and agents is directed towards decommodification of the product, either through differentiated products, differentiated processes or through differentiated channels of distribution, associating rural and non-rural production. On the one hand, the creation of such differentiation involves the realization of innovations, and through them higher value products are added. On the other hand, the continuity of these subsystems depends on the return of efforts in innovation. Therefore, since they involve greater asset specificity and quality attributes that may not be easily measurable, more complex governance structures are needed. Thus, the purpose of this study was to understand how the governance structures between producers and cooperatives influence, ex ante, innovation, and, ex post, the distribution of value generated, in beef differentiated agri-food systems in Paraná. In order to reach the research objective, the present study, based on a cross-sectional study, was based on Transaction Costs Economics (WILLIAMSON, 1985, 1991), the Measurement Costs Economics (BARZEL, 1985; and concepts and definitions on Innovation (Schumpeter, 1997, OCDE, 1997, FREEMAN, SOETE, 2008). The qualitative and descriptive research comprised the collection of secondary and primary data. Data collection involved, in addition to the analysis of documents such as invoices, manuals and fiscal notes, semi-structured interviews with key agents, producers and representatives of two cooperatives focused on the differentiated livestock of Paraná State. Data analysis was performed using the content analysis technique with Atlas.TI® software support. As results, it was identified that the governance structure adopted between producers and cooperatives was the hybrid form by verbal agreement based on the relational aspect. Ex ante, it was possible to identify that although the governance structure promoted innovation through the exchange of experience among cooperative members, the first case analyzed participated passively in this innovation process, while in the second case the cooperative participated actively. The second cooperative analyzed fostered innovations, as well as the exchange of experience among the members of the cooperative, through training, courses and technical assistance. From the attributes of transaction and dimensions of the asset, it was possible to verify that the governance structure is in line with the assumptions of TCE and MCE. However, since producers are remunerated only by gender, minimum standard of fat covering and final carcass weight, it has been found that there are shortcomings in the distribution of value to producers. Thus, it is concluded that although in the short term the analyzed cases involve failures in the distribution of value, due to the non-remuneration of quality attributes such as race, marbling and precocity, it was observed that the perpetuation of such subsystems depends, in the long run, on the realization of innovations.